A retrospective pilot study to determine whether the reproductive tract microbiota differs between women with a history of infertility and fertile women. (26th December 2017) - Wee, Bryan A.; Thomas, Mark; Sweeney, Emma Louise; Frentiu, Francesca D.; Samios, Melanie; Ravel, Jacques; Gajer, Pawel; Myers, Garry; Timms, Peter; Allan, John A.; Huston, Wilhelmina M.
Abstract : Background: We know very little about the microbiota inhabiting the upper female reproductive tract and how it impacts on fertility. Aims: This pilot study aimed to examine the vaginal, cervical and endometrial microbiota for women with a history of infertility compared to women with a history of fertility. Materials and methods: Using a retrospective case–control study design, women were recruited for collection of vaginal, cervical and endometrial samples. The microbiota composition was analysed by 16S ribosomal RNA (rRNA) gene amplification and endometrial expression of selected human genes by quantitative reverse transcription polymerase chain reaction. Results: Sixty‐five specimens from the reproductive tract of 31 women were successfully analysed using 16S rRNA gene amplicon sequencing (16 controls and 15 cases). The dominant microbial community members were consistent in the vagina and cervix, and generally consistent with the endometrium although the relative proportions varied. We detected three major microbiota clusters that did not group by tissue location or case–control status. There was a trend that infertile women more often had Ureaplasma in the vagina and Gardnerella in the cervix. Testing for the expression of selected genes in the endometrium did not show evidence of correlation with case–control status, or with microbial community composition, although Tenascin‐C expression correlated with a history of miscarriage. Conclusions: There is a need for further exploration of the endometrial microbiota, and how the microbiota members or profile interplays with fertility or assisted reproductive technologies.